(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical, paraclinical characteristics and quality of life of patients with chronic obstructive pulmonary disease at Friendship Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 60 patients diagnosed with stable chronic obstructive pulmonary disease who were being managed at the Respiratory and Allergy Department, Friendship Hospital, from November 2024 to April 2025. Result: 93.3% of patients had been exposed to cigarette smoke. According to the ABE classification: group E (76.7%), group B (16.7%), group A (6.6%). 41.7% of patients had chronic obstructive pulmonary disease for more than 10 years, 33.3% had chronic obstructive pulmonary disease for 5-10 years, and the remainder had chronic obstructive pulmonary disease for less than 5 years. 51.7% of patients were using their chronic obstructive pulmonary disease prophylactic inhaler incorrectly. Dyspnea on exertion (73.3%), cough (58.3%), sputum production (46.7%), chest tightness (20%), decreased pulmonary ventilation (86.7%). Stage classification according to FEV1: mainly in the moderate (46.7%) and severe (38.3%) stages. Chest X-ray characteristics: widened intercostal spaces (90%) and dirty lung appearance (75%). Chest CT characteristics: most common findings were alveolar dilation (73.3%) and bronchiectasis (26.7%). Increased pulmonary artery pressure accounted for 36.4% of cases. 33.3% of patients had eosinophils above 300 cells/μL. Quality of life of COPD patients according to the SGRQ-C scale: general, symptoms, activity, impact were 1.18 ± 22.90; 58.83 ± 22.74; respectively. 56.90 ± 22.59; 44.53 ± 24.49. Consclusion: Most patients with stable chronic obstructive pulmonary disease at Friendship Hospital are in group E with moderate to severe FEV1; a high percentage have had the disease for more than 5 years. Common clinical symptoms include: shortness of breath on exertion, cough, and sputum production. Many patients have emphysema, pulmonary hypertension, and eosinophilia. Quality of life is reduced.